Perencanaan Strategi Preventive Maintenance Pada Mesin Shot Blasting di PT. ABC dengan Klasifikasi ISMO - Herman Budi Harja; Aditya Riyanto Putra; Wibawa Kresnandi (Pusat Pengembangan, Penelitian dan Pengabdian kepada Masyarat (P4M) Politeknik Manufaktur Bandung (Polman Bandung), 2021)
A shot blasting machine is a cleaning machine for casting products with a steel ball shooting mechanism from the impeller/blast wheel rotation's centrifugal force. As the main machine in the final process of casting production activities, the decrease in machine reliability has a negative impact on the production system. Currently, the production equipment maintenance strategy at PT ABC is still implementing corrective maintenance, which is unplanned and reactive when a machine malfunction occurs. It resulted in high production loss and increased maintenance costs. Therefore, the shot blasting machine's maintenance strategy should be changed to a type of preventive maintenance. This study aims to plan preventive maintenance (PM) system for the shot blasting machines of PT. ABC, such as creating PM schedule, calculating machine downtime, and technician needs for each PM activity. PM system planning is achieved using the ISMO (Inspection, Small repair, Medium repair, and Overhaul) method. Its method was conducted in several stages, which start with identifying machine objects, making PM work specifications, determining the value of mark complexity and maintenance cycle, calculating machine downtime and technician needs. Then making schedules annual and monthly, and several other maintenance documents. The mechanism for determining the complexity value is determined based on the similarity of the HP Garg methodology's machine specifications. Finally, The planning of the shot blasting machine PM system has been successfully done, some of the PM information obtained are (i) the machine maintenance cycle is C - I1 - I2 - S1 - I3 - I4 - M1 - I5 - I6 - S2 - I7 - I8 - M2 - I9 - I10 - S3 - I11 - I12 - C, (ii) the time interval between maintenance activities is one month, (iii) machine downtime for each shot blasting machine, (iV) the number and level of maintenance technicians required in every ISMO activity for drum shot, batch shot and hanger shot machines. The calculating verification of the shot blasting machine's availability value on the proposed PM schedule shows that machine availability increased to more than 80%.